Assessment of nutritional status, obesity, and metabolic syndrome among uniformed personnel in Kota Bharu, Kelantan - Bakar, Nur Amalina Abu (Universiti Sains Malaysia, 2013)
Obesity is currently one of leading risk to global health which has reached epidemic prevalence of metabolic syndrome (MetS) worldwide had also become a part of an important health problem, leading to early mortality rate among adults. The objective of this cross sectional study is to determine the prevalence of obesity and metabolic syndrome among systematically selected uniformed personnel from Kota Bharu, Kelantan. A total of 136 uniformed personnel (87 male and 49 female) aged between 26 to 58 years old participated in this study, and the prevalence of MetS was determined according to the IDF definition. Weight, height, body mass index (BMI), waist and hip circumference, skinfold, blood lipid profile and plasma fasting glucose were measured, in addition to the administration of socio-demographic questionnaires, Knowledge, Attitude and Practice (KAP) on food and nutrition, International Physical Activity Questionnaires (IPAQ) and Food Frequency Questionnaire (FFQ). The MetS prevalence among the uniformed personnel by IDF definition was 17.6%, with 17.2% and 18.4% for male and female, respectively. The mean BMI ± SD was 26.3 ± 4.3 and the mean BMI for male and female were 26.8 ± 4.2 and 25.3 ± 4.3, respectively. About 1.5% was underweight, 39.0% was normal, 41.9% was overweight, and 17.6% was obese. The iv proportion which linked to more deaths worldwide than underweight. The increased results showed high prevalence of overweight and obesity as well as the prevalence of metabolic syndrome which found quite high among the uniformed personnel. This suggests that obesity and MetS prevalence is increasing in Malaysia population regardless the occupation type. The proper intervention as well as changing in the lifestyle behavior including the diet and physical activity should be implemented.